THE EFFECT OF SOCIAL MEDIA MARKETING AND SERVICE QUALITY ON PURCHASE DECISIONS ON NETFLIX STREAMING SERVICES WITH PERCEPTION MEDIATION - Ranti Cahyati; Komsi Koranti; Aji Sukarno; Fani Yulia Rosyada (SEAN Institute, 2023)
The purpose of this study is to analyze the effect of social media marketing and service quality on purchasing decisions on Netflix streaming services by mediating brand perception. The analytical method in this study uses qualitative primary data. The data used in this study using a questionnaire instrument and valid data collected as many as 120 respondents. The sampling method in this research is purposive sampling. The analytical tool used is PLS (Partial Least Square). The test stages carried out are: convergent validity test, discriminant validity test, composite reliability test, Cronbach’s alpha test, coefficient of determination test (R2), predictive relevance (Q²), goodness of fit (GoF) and hypothesis testing. The testing tool used is SmartPLS. The results show that social media marketing and service quality affect brand perceptions, but social media marketing does not affect purchasing decisions, service quality and brand perceptions affect purchasing decisions, social media marketing and service quality affect purchasing decisions by mediating brand perceptions.